Fairy Tales Framed : Early Forewords, Afterwords, and Critical Words - Bottigheimer, Ruth B. (Book collections on Project MUSE., 2012)
"Translations of the forewords and afterwords by original fairy tale authors and commentaries by their contemporaries, material that has not been widely published in English."--Project Muse